THE EFFECT OF EXCHANGE RATES, EXPORTS AND IMPORTS ON ECONOMIC GROWTH IN INDONESIA - Ema Nopiana; Zannur Habibah; Widya Amanda Putri (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
The country's economic growth can be seen from the price of gross domestic product (GDP). Gross domestic product can be used as one of the benchmarks in fostering economic improvement from various sectors indirectly. Economic growth is stimulated through various factors, including import prices as well as changes in the price of the rupiah or the exchange rate of the rupiah. This study aims to determine the impact of exports and imports on financial improvement in Indonesia. This research technique uses a quantitative approach. The records received in this observation are secondary records received from the World Bank in the form of time collection from 1989 to 2018. Data evaluation is carried out through more than one regression evaluation with the help of time series tools. The results of the study reveals that the exchange rate and import variables have a major effect on economic growth. Meanwhile, the export variable has a negative impact on economic growth.